Postoperative pneumonia in isolated coronary artery bypass grafting: A comprehensive study of epidemiology, etiology, and disease burden from China (2020–2023) - Yuxiao Zhan; Jian Zhang; Yang Yang; Rui Yang; Guojun Zhang (PLoS ONE, 2025)
Objective To investigate the epidemiological trends,etiological profiles and disease burden metrics related to postoperative pneumonia following isolated coronary artery bypass grafting (CABG). Methods A retrospective analysis was conducted on data from 518 patients who developed postoperative pneumonia following isolated CABG between January 1, 2020, and November 30, 2023. Results Postoperative pneumonia occurred at a rate of 11.34% among the cohort (518/4569),which fluctuated by year (P < 0.001). Patients aged 60–80 and over 80 years exhibited significantly higher incidence rates compared to those under 60 years (all P < 0.05) A total of 416 strains were identified, with Gram-negative bacteria accounting for 86.5%, primarily represented by Klebsiella pneumoniae (31.0%), while pseudomonas aeruginosa (21.4%) and stenotrophomonas maltophilia (5.3%) demonstrated an increasing trend in the period of 2022–2023 (both P < 0.05). The proportion of Staphylococcus aureus in the fourth quarter was significant lower than that in the first quarter (4.8% vs 14.4%, P < 0.05). The overall detection rate of multi-drug resistant organisms (MDRO) was 57.7%,with 53.9% for Gram-negative bacteria and 82.1% for Gram-positive bacteria.Late-onset postoperative pneumonia was significantly associated with a higher detection rate of MDRO (63.8% vs 50.3%, P < 0.01). Postoperative pneumonia prolonged median length of postoperative hospital[20.00 (13.00,31.25) days vs 15.50(10.25,19.75) days, P < 0.001] and ICU [9.00(5.00,14.00)days vs 4.00(3.00,11.75) days, P = 0.002] stay, thereby increasing hospitalization costs[￥255592.15 (193384.29, 336337.53) vs ￥180501.02 (154493.58, 220501.03),P < 0.001]. The incidence of severe pneumonia significantly increased in patients infected with MDRO (19.30% vs. 5.51%, P < 0.001) or co-infected (40.00% vs. 9.52%, P < 0.001), leading to marked differences in postoperative hospital stay and hospitalization costs (all P < 0.05). Conclusion The etiological patterns of postoperative pneumonia following isolated CABG showed temporal variations by year and quarter. MDRO infection and co-infections could significantly exacerbate the disease burden on patients.